СОЦИАЛ ИНТТЕЛЛЕКТ ТИББИЁТ ХОДИМЛАРИ КАСБИЙ КОМПЕТЕНТЛИГИНИНГ МУҲИМ ОМИЛИ СИФАТИДА - Собирова, Д.А. (SCIENCE and SOCIETY, 2019)
The article is devoted to the discussion of the relationship between social intelligence, professionalism, and the competence of medical personnel.
Keywords: social intellect; professional competence; professional skills; professional position; cognitive; emotional; social flexibility; КОСКОМ-2